IMIGRAÇÃO E EDUCAÇÃO DOS POLONESES EM PONTA GROSSA, PR - Kubaski, Luciana (2015)
This study aimed to analyze the process of institutionalization of the first Polish schools ran by religious congregations in Ponta Grossa, Paraná. It presents a historical reconstruction of the immigration of Europeans to Brazil from 1850 on, until the first decades of the XX century. In this period there were several immigration movements from Europe to Brazil, which were encouraged by the Brazilian government as a solution of problems related to workforce and land occupation, but also met the interests of thousands of people from other countries, who expected to find a more promising future in Brazil than that offered by their countries of origin, mainly the dream of having their own piece of land. Immigrants from different ethnic groups entered the country and spread over the Brazilian territory. Many started working on the developing coffee farms; others occupied the empty areas in the South of the country adopting the family farming system. A great number of Polish people settled in Paraná, and as soon as they arrived (together with other measures) they founded schools for their children. In Ponta Grossa, the catholic schools, ColégioSanta‟Ana and ColégioSagradaFamília were started as an initiative of the religious congregation of the Sisters Servants of the Holy Spirit and were later on taken over by the Holy Family Congregation. In order to answer the research questions, the analysis categories selected were: society, State, education and immigration. The theoretical-methodological basis is the historical dialectical materialism, which allows understanding and apprehension of the reality. The research surveyed documents such as the Paraná province president reports, laws, decrees, essays and photos as primary sources, aiming to approach the whole of the object studied. The investigation carried out led to the comprehension that the foundation of schools for the children of Polish immigrants had its origin in the struggles experienced within the Catholic Church as a result of the Romanization process. The arrival of the Holy Family Congregation to the city of Ponta Grossa became an important element, which united the Polish community around the catholic faith and, therefore, guaranteed the power and expansion of this Church in the Campos Gerais region.